The Study on Characteristics of Heat Treatment of The AA2024 Aluminum Alloys - Fatima Ezzohra El Garchani; Moulay Rachid Kabiri (Pandawa Institute, 2023)
This study examined the behavior of AA2024 aluminum alloys, which received different heat treatments, i.e., homogenization, quenching, artificial aging, and recrystallization. The homogenization temperature is set at 495 °C for 5 hours and followed by slow cooling in the furnace. Then a quenching treatment was done with cold water. Artificially aged alloys were heated to 495 °C for 5 hours, followed by rapid water cooling, then heating to 140 °C for 2 hours, and followed by slow cooling in the furnace. The recrystallization treatment was also studied by heating the solution to 495 °C for 5 hours, followed by rapid cooling with cold water and heating to 310 °C for 3 hours in the furnace. In this study, we used an optical microscope and a scanning electron microscope to analyze the microstructures of the samples. X-ray fluorescence analysis was used to determine the proportion of each element on the surface of each alloy. Phase and structural analyses were performed by X-ray diffraction while the mass loss was calculated after 60 hours of exposure for all samples in a climate chamber. Our work revealed that the rate of mass loss could decrease with heat treatment of the alloy due to the emergence of additional phases and dispersoids. The result showed that the surface fraction of each element was changed due to heat treatment in an aggressive environment, in which the Al2Cu and Al2CuMg phases disappeared after the solution treatment as revealed from the XRD data.